Preparation method and application of polypyrrole-derived porous carbon material

By using polypya -derived porous carbon material modified zinc negative electrodes, the growth, corrosion and hydrogen analysis of the zinc -ion battery in the water system, and realized the significant extension and stability improvement of the battery life.

CN119349544AActive Publication Date: 2025-01-24HARBIN INST OF TECH +1
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202411430025.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-14
Publication Date
2025-01-24
Estimated Expiration
2044-10-14

AI Technical Summary

Technical Problem

In practical applications, aqueous zinc ion batteries face dendritic growth, corrosion and hydrogen evolution problems, resulting in short circuits and shortened battery life.

Method used

Polypyrrole-derived porous carbon material is used as a modified material for the zinc anode. It is prepared by potassium permanganate etching to form a nitrogen-doped structure with enriched pyridinic nitrogen and a large number of defects. The nitrogen doping type and defect content are adjusted to improve zinc Ion enrichment and desolvation, reducing free water content, inhibiting dendrite growth and corrosion.

Benefits of technology

It significantly improves the dendrite problem of the zinc anode, extends the cycle life of the battery, has a stable cycle of more than 2,000 hours, and improves the stability and corrosion resistance of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119349544A_ABST
    Figure CN119349544A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method and application of a polypyrrole-derived porous carbon material, and relates to a preparation method and application of a porous carbon material. The invention aims to solve the problems of short circuit and short service life of the battery caused by dendritic crystal growth, corrosion and hydrogen evolution of the current aqueous zinc ion battery in practical application. According to the invention, pyrrole is used as a precursor, and the porous carbon material is prepared through potassium permanganate etching; the porous carbon material has a nitrogen-doped structure with enriched pyridine nitrogen and a large number of defects; by controlling the etching time, the nitrogen doping type and the defect content can be accurately adjusted; wherein the doped nitrogen element contains pyridine nitrogen and pyrrole nitrogen structures with zinc affinity, so that zinc ions can be effectively enriched. The prepared zinc negative electrode with the porous carbon coating on the surface has the advantages of being long in cycle life and good in stability, the coating preparation process is simple, and the zinc negative electrode has industrialization prospects.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a preparation method and application of a porous carbon material. Background Art

[0002] With the development of the global economy, the consumption of fossil fuels has continued to increase. Although this has promoted the progress of human society, it has also led to serious ecological damage. Since traditional fossil energy sources such as coal and oil are non-renewable, the risk of energy depletion is becoming increasingly apparent. Against this background, green renewable energy sources such as solar energy and wind energy have gradually emerged and shown great future potential. However, the output of new energy is easily affected by seasons, climate and geographical location, and there is instability, which may lead to an imbalance in energy supply and demand and power fluctuations in the power grid. In order to solve this problem, various energy storage technologies have been developed to convert electrical energy into mechanical energy, chemical energy and other forms of storage to ensure a reliable supply of energy.

[0003] In the field of energy storage, zinc-ion batteries are gradually gaining attention because they use aqueous electrolytes, have the advantages of high safety and low cost. Compared with lithium-ion batteries, zinc-ion batteries avoid the safety hazards brought by flammable electrolytes, and zinc resources are more widely distributed, reducing the risk of supply chain dependence. Although lithium-ion batteries have a high energy density, their safety and cost limit their application in large-scale energy storage. Zinc-ion batteries have shown broader application prospects in the field of new energy storage due to their improved energy density and power density, becoming an ideal alternative energy storage system.

[0004] With the deepening of zinc ion battery research, people have found that the performance of aqueous zinc ion batteries is increasingly limited by the metal zinc negative electrode, which seriously hinders its large-scale application in the field of energy storage. First, the zinc electrode is prone to form a rough and uneven surface during the charge and discharge process. With the increase in the number of cycles, the deposition and dissolution of the negative electrode metal ions lead to the formation of dendrites. Secondly, these dendrites may not only pierce the diaphragm and cause a short circuit, but also fall off into the electrolyte, resulting in the loss of electrical contact and conversion into inactive dead zinc, which significantly affects the reversible capacity, coulombic efficiency and cycle stability of the battery. In addition, the zinc electrode will suffer from corrosion when exposed to the electrolyte for a long time, produce hydrogen and consume electricity, and ultimately shorten the service life of the battery. Therefore, the development of a new dendrite-free negative electrode material is one of the keys to promote the large-scale application of aqueous zinc ion batteries. Summary of the invention

[0005] The purpose of the present invention is to solve the problems of dendrite growth, corrosion and hydrogen evolution faced by aqueous zinc ion batteries in practical applications, which in turn cause battery short circuit and shortened life, and to provide a preparation method and application of a polypyrrole-derived porous carbon material.

[0006] A method for preparing a polypyrrole-derived porous carbon material is specifically completed in the following steps:

[0007] 1. Add methyl orange to deionized water, and then stir in a water bath until the methyl orange is completely dissolved to obtain a methyl orange solution;

[0008] 2. adding pyrrole monomer to methyl orange solution and stirring magnetically to obtain a mixed solution;

[0009] 3. Add ferric chloride to deionized water and stir magnetically to obtain a ferric chloride solution;

[0010] 4. Under magnetic stirring conditions, adding the ferric chloride solution dropwise into the mixed solution, continuing magnetic stirring, to obtain a solid reactant I; washing and drying the solid reactant I, to obtain a solid reactant II;

[0011] 5. Adding solid reactant II into deionized water under ultrasonic conditions, and dispersing by ultrasonication to obtain a dispersion; adding potassium permanganate solution and concentrated sulfuric acid to the dispersion in sequence under stirring conditions, and performing stirring and etching to obtain solid reactant III;

[0012] 6. Clean and dry the solid reactant III to obtain a solid reactant IV; transfer the solid reactant IV to a tubular furnace, heat it to a calcination temperature under the protection of an inert gas atmosphere, calcine it at the calcination temperature for a period of time, grind it into particles after calcination, and obtain a polypyrrole-derived porous carbon material.

[0013] A polypyrrole-derived porous carbon material is used to modify zinc anode.

[0014] Beneficial effects of the present invention:

[0015] 1. The present invention uses pyrrole as a precursor and prepares a porous carbon material by potassium permanganate etching; the porous carbon material has a nitrogen-doped structure with enriched pyridinic nitrogen and a large number of defects; by controlling the etching time, the nitrogen doping type and defect content can be accurately adjusted; wherein, the doped nitrogen element contains pyridinic nitrogen and pyrrolic nitrogen structures with zinc-philic properties, which can effectively enrich zinc ions; combined with the hydrophobic properties of the carbon material, the porous carbon material prepared by this method helps to form a local environment rich in desolvated zinc ions and containing less free water between the carbon material protective layer and the metal zinc negative electrode; in this environment, the deposited layer of the metal zinc negative electrode will spontaneously expose more (002) crystal planes, thereby inducing the deposited layer to preferentially and directional deposit along the dendrite-free (002) crystal plane in subsequent charge and discharge cycles, effectively improving the dendrite problem of the metal zinc negative electrode; in addition, since the free water content in the local interface area contacted by the metal zinc negative electrode is significantly reduced, the hydrogen evolution reaction and corrosion problems caused by this can also be effectively alleviated;

[0016] Second, the Zn / / Zn symmetric battery assembled with the modified zinc anode (zinc anode with porous carbon coating on the surface) can be used at 2mA / cm 2 The battery can be stably cycled for more than 2000 h at a current density of 2000 h, which is much longer than the symmetrical battery life assembled with unmodified zinc anode (original zinc anode).

[0017] 3. The zinc negative electrode with a porous carbon coating on the surface prepared by the present invention has the advantages of long cycle life and good stability, and the coating preparation process is simple and has industrial prospects.

[0018] The invention can obtain a polypyrrole-derived porous carbon material and a zinc negative electrode with a porous carbon coating on the surface. The zinc negative electrode with a porous carbon coating on the surface is used as a negative electrode of an aqueous zinc ion battery. BRIEF DESCRIPTION OF THE DRAWINGS

[0019] Figure 1 A scanning electron microscope image of the polypyrrole-derived porous carbon material prepared in Example 1;

[0020] Figure 2 This is a scanning electron microscope image of the surface of the zinc negative electrode having a porous carbon coating prepared in Example 2;

[0021] Figure 3 This is an X-ray photoelectron spectrum of the polypyrrole-derived porous carbon material prepared in Example 1;

[0022] Figure 4 The symmetrical cell assembled with the unmodified zinc anode and the zinc anode with a porous carbon coating prepared in Example 2 was tested at 2 mA / cm 2 、1mAh / cm 2 Time voltage graph under test conditions;

[0023] Figure 5 This is a scanning electron microscope image of the polypyrrole-derived carbon material prepared in Example 3;

[0024] Figure 6 This is a scanning electron microscope image of the polypyrrole-derived carbon material prepared in Example 4;

[0025] Figure 7 The symmetrical battery assembled with the zinc negative electrode having a porous carbon coating on the surface prepared in Example 5 was charged at 2 mA / cm 2 、1mAh / cm 2 Time voltage graph under test conditions;

[0026] Figure 8 The symmetrical battery assembled with the zinc negative electrode having a porous carbon coating on the surface prepared in Example 6 was 2 、1mAh / cm 2Time-voltage graph under test conditions. DETAILED DESCRIPTION

[0027] The following examples further illustrate the content of the present invention, but should not be construed as limiting the present invention. Without departing from the essence of the present invention, modifications and substitutions made to the methods, steps or conditions of the present invention all fall within the scope of the present invention.

[0028] Specific implementation method 1: This implementation method is a method for preparing a polypyrrole-derived porous carbon material, which is specifically completed in the following steps:

[0029] 1. Add methyl orange to deionized water, and then stir in a water bath until the methyl orange is completely dissolved to obtain a methyl orange solution;

[0030] 2. adding pyrrole monomer to methyl orange solution and stirring magnetically to obtain a mixed solution;

[0031] 3. Add ferric chloride to deionized water and stir magnetically to obtain a ferric chloride solution;

[0032] 4. Under magnetic stirring conditions, adding the ferric chloride solution dropwise into the mixed solution, continuing magnetic stirring, to obtain a solid reactant I; washing and drying the solid reactant I, to obtain a solid reactant II;

[0033] 5. Adding solid reactant II into deionized water under ultrasonic conditions, and dispersing by ultrasonication to obtain a dispersion; adding potassium permanganate solution and concentrated sulfuric acid to the dispersion in sequence under stirring conditions, and performing stirring and etching to obtain solid reactant III;

[0034] 6. Clean and dry the solid reactant III to obtain a solid reactant IV; transfer the solid reactant IV to a tubular furnace, heat it to a calcination temperature under the protection of an inert gas atmosphere, calcine it at the calcination temperature for a period of time, grind it into particles after calcination, and obtain a polypyrrole-derived porous carbon material.

[0035] Specific embodiment 2: This embodiment differs from specific embodiment 1 in that the concentration of the methyl orange solution in step 1 is 5 mmol / L to 10 mmol / L, and the temperature of the water bath heating in step 1 is 60° C. to 80° C. The other steps are the same as those in specific embodiment 1.

[0036] Specific embodiment 3: This embodiment differs from specific embodiment 1 or 2 in that: the volume ratio of the pyrrole monomer to the methyl orange solution in step 2 is (300 μL-400 μL): (80 mL-120 mL); the speed of the magnetic stirring in step 2 is 800 r / min-1000 r / min, and the magnetic stirring time is 60 min-90 min. The other steps are the same as those in specific embodiment 1 or 2.

[0037] Specific embodiment 4: This embodiment differs from specific embodiments 1 to 3 in that the concentration of the ferric chloride solution in step 3 is 40 mmol / L to 60 mmol / L; the speed of the magnetic stirring in step 3 is 500 r / min to 1000 r / min, and the time of the magnetic stirring is 10 min to 30 min. The other steps are the same as those in specific embodiments 1 to 3.

[0038] Specific embodiment 5: This embodiment differs from specific embodiments 1 to 4 in that: the volume ratio of the ferric chloride solution described in step 4 to the methyl orange solution in the mixed solution is (15mL to 25mL): (80mL to 120mL); the speed of the continuous magnetic stirring described in step 4 is 700r / min to 900r / min, and the time of continuous magnetic stirring is 24h to 36h; in step 4, deionized water is used to wash the solid reactant I 3 to 5 times; the drying temperature described in step 4 is 70℃ to 90℃, and the drying time is 8h to 10h. The other steps are the same as those of specific embodiments 1 to 4.

[0039] Specific implementation method 6: The difference between this implementation method and specific implementation methods 1 to 5 is that: the power of the ultrasonic dispersion described in step 5 is 160W~180W, and the ultrasonic dispersion time is 60min~90min; the mass ratio of the solid reactant II in the dispersion described in step 5 to the volume of deionized water is (350mg~450mg):(35mL~45mL); the concentration of the potassium permanganate solution described in step 5 is (20mmol / L~30mmol / L); the volume ratio of the potassium permanganate solution described in step 5 to the dispersion is (50mL~70mL):(30mL~50mL); the volume ratio of the concentrated sulfuric acid described in step 5 to the volume ratio of the potassium permanganate solution is (500μL~600μL):(50mL~60mL); the mass fraction of the concentrated sulfuric acid is 90%~98%; the stirring etching time described in step 5 is 3h~6h. The other steps are the same as specific implementation methods 1 to 5.

[0040] Specific embodiment 7: This embodiment differs from specific embodiments 1 to 6 in that: in step 6, deionized water is used to wash the solid reactant III until it is colorless and neutral; the drying temperature in step 6 is 60°C to 80°C, and the drying time is 10h to 16h; the heating rate in step 6 is 2°C / min to 10°C / min; the calcination temperature in step 6 is 700°C to 900°C, and the calcination time is 60min to 100min; the inert gas in step 6 is nitrogen, argon or helium. The other steps are the same as those in specific embodiments 1 to 6.

[0041] Specific implementation method eight: This implementation method is a polypyrrole-derived porous carbon material used to modify the zinc negative electrode.

[0042] Specific embodiment 9: This embodiment differs from specific embodiments 1 to 8 in that: a polypyrrole-derived porous carbon material is used to modify the zinc negative electrode, which is specifically completed by the following steps:

[0043] 1. dispersing a polypyrrole-derived porous carbon material and a binder in a solvent to obtain a dispersion;

[0044] The solvent in step 1 is one or a mixture of several of N-methylpyrrolidone, dimethyl sulfoxide, acetonitrile, dichloromethane and ethanol;

[0045] The binder in step 1 is one or a mixture of polyvinylidene fluoride, polyacrylic acid and polyurethane;

[0046] The mass ratio of the polypyrrole-derived porous carbon material to the binder in step 1 is (8-9):(1-2);

[0047] Step 1: The mass fraction of the polypyrrole-derived porous carbon material in the dispersion is 60% to 70%;

[0048] 2. coating the dispersion onto the surface of the zinc negative electrode and drying it to obtain a zinc negative electrode having a porous carbon coating on the surface;

[0049] The drying temperature in step 2 is 60°C to 80°C;

[0050] In step 2, the thickness of the porous carbon coating on the surface of the zinc negative electrode is 5 μm to 30 μm. The other steps are the same as those in specific embodiments 1 to 8.

[0051] Specific embodiment 10: This embodiment differs from specific embodiments 1 to 9 in that the zinc negative electrode with a porous carbon coating on the surface is used as the negative electrode of the aqueous zinc ion battery. The other steps are the same as those of specific embodiments 1 to 9.

[0052] The following examples are used to verify the beneficial effects of the present invention:

[0053] Example 1: A method for preparing a polypyrrole-derived porous carbon material, which is specifically completed in the following steps:

[0054] 1. Add methyl orange to deionized water, and then stir in a water bath at 80°C until the methyl orange is completely dissolved to obtain a methyl orange solution;

[0055] The concentration of the methyl orange solution described in step 1 is 5 mmol / L;

[0056] 2. Add 350 μL of pyrrole monomer into 100 mL of methyl orange solution, and stir the mixture for 60 min at a magnetic stirring speed of 800 r / min to obtain a mixed solution;

[0057] 3. Add ferric chloride to deionized water, and then stir the mixture under magnetic stirring at a speed of 1000 r / min for 30 min to obtain a ferric chloride solution;

[0058] The concentration of the ferric chloride solution described in step 3 is 50mmol / L;

[0059] 4. Under the condition of magnetic stirring at a speed of 800 r / min, 20 mL of ferric chloride solution was added dropwise to the mixed solution obtained in step 2, and magnetic stirring was continued for 24 h under the condition of magnetic stirring at a speed of 800 r / min to obtain solid reactant I; solid reactant I was washed 3 times with deionized water, and then dried at 70° C. for 10 h to obtain solid reactant II;

[0060] 5. Add 400 mg of solid reactant II to 40 mL of deionized water under ultrasonic conditions, and disperse by ultrasonication to obtain a dispersion; add 60 mL of potassium permanganate solution and 530 μL of concentrated sulfuric acid to the dispersion in sequence under stirring conditions, and stir and etch for 3 hours to obtain a solid reactant III;

[0061] The power of the ultrasonic dispersion in step 5 is 180 W, and the ultrasonic dispersion is performed for 90 min;

[0062] The concentration of the potassium permanganate solution described in step 5 is 25mmol / L;

[0063] The mass fraction of the concentrated sulfuric acid described in step 5 is 98%;

[0064] 6. Wash the solid reactant III with deionized water until it is colorless and neutral, and dry it at 70° C. for 10 hours to obtain a solid reactant IV; transfer the solid reactant IV to a tube furnace, raise the temperature to 800° C. under the protection of an inert gas atmosphere, and calcine at 800° C. for 80 minutes to obtain a polypyrrole-derived porous carbon material;

[0065] The heating rate in step 6 is 5°C / min;

[0066] The inert gas described in step six is ​​nitrogen.

[0067] Example 2: A polypyrrole-derived porous carbon material prepared in Example 1 is used to modify a zinc negative electrode, specifically by the following steps:

[0068] 1. Dispersing 90 mg of the polypyrrole-derived porous carbon material prepared in Example 1 and polyvinylidene fluoride in 100 μL of N-methylpyrrolidone to obtain a dispersion;

[0069] The mass ratio of the polypyrrole-derived porous carbon material to polyvinylidene fluoride described in step 1 is 9:1;

[0070] 2. Use sandpaper to polish the zinc negative electrode with a thickness of 100 μm to make it bright, remove the oxide layer, adjust the coating thickness of the coater to 150 μm, and then apply the dispersion to the surface of the polished zinc negative electrode, and dry it at 80°C for 12 hours to obtain a zinc negative electrode with a porous carbon coating on the surface;

[0071] In step 2, the thickness of the porous carbon coating on the surface of the zinc negative electrode is 15 μm.

[0072] Figure 1 A scanning electron microscope image of the polypyrrole-derived porous carbon material prepared in Example 1;

[0073] from Figure 1 It can be seen that the polypyrrole-derived porous carbon material prepared in Example 1 has a porous structure.

[0074] Figure 2 This is a scanning electron microscope image of the surface of the zinc negative electrode having a porous carbon coating prepared in Example 2;

[0075] from Figure 2 It can be seen that the polypyrrole-derived porous carbon material is evenly distributed on the surface of the zinc negative electrode.

[0076] Figure 3 This is an X-ray photoelectron spectrum of the polypyrrole-derived porous carbon material prepared in Example 1;

[0077] from Figure 3 The main element composition of polypyrrole-derived porous carbon materials can be seen, among which there is obvious nitrogen doping.

[0078] The symmetrical battery assembled using the zinc negative electrode with a porous carbon coating on the surface prepared in Example 2 is specifically completed by the following steps:

[0079] ①, punching the zinc negative electrode with a porous carbon coating on the surface prepared in Example 2 into a disc with a diameter of 14 mm by a punching machine, as an electrode sheet of a symmetrical battery;

[0080] ② Use a punching machine to punch the glass fiber into discs with a diameter of 16 mm as a diaphragm;

[0081] ③. The electrolyte is 2mol / L zinc sulfate electrolyte;

[0082] ④. Place the battery pole piece and diaphragm in the button battery negative electrode shell in order, add 70 microliters of electrolyte to wet the diaphragm, then add the other side electrode piece, stainless steel gasket, spring and button battery positive electrode shell, and then use a sealing machine at 50kg / cm 2 Button symmetrical battery encapsulated under pressure.

[0083] Figure 4 The symmetrical cell assembled with the unmodified zinc anode and the zinc anode with a porous carbon coating prepared in Example 2 was tested at 2 mA / cm 2 、1mAh / cm 2 Time voltage graph under test conditions;

[0084] from Figure 4 It can be seen that compared with the symmetrical battery composed of untreated pure zinc sheets, the cycle life of the symmetrical battery composed of the zinc negative electrode modified with polypyrrole-derived porous carbon material is significantly improved, with a stable cycle of more than 2800 hours. During the entire cycle, there is no obvious fluctuation in the polarization voltage, which strongly proves the cycle stability of the modified zinc negative electrode.

[0085] Example 3: The preparation method of polypyrrole-derived carbon material is specifically completed by the following steps:

[0086] 1. Add 350 μL of pyrrole monomer into 100 mL of deionized water, and stir the mixture for 60 min at a magnetic stirring speed of 800 r / min to obtain a pyrrole solution;

[0087] 2. Add ferric chloride to deionized water, and then stir the mixture under magnetic stirring at a speed of 1000 r / min for 30 min to obtain a ferric chloride solution;

[0088] The concentration of the ferric chloride solution described in step 2 is 50mmol / L;

[0089] 3. Under the condition of magnetic stirring at a speed of 800 r / min, 20 mL of ferric chloride solution was added dropwise to the pyrrole solution, and magnetic stirring was continued for 24 h under the condition of magnetic stirring at a speed of 800 r / min to obtain solid reactant I; solid reactant I was washed 3 times with deionized water, and then dried at 70°C for 10 h to obtain solid reactant II;

[0090] 4. Add 400 mg of solid reactant II to 40 mL of deionized water under ultrasonic conditions, and disperse by ultrasonication to obtain a dispersion; add 60 mL of potassium permanganate solution and 530 μL of concentrated sulfuric acid to the dispersion in sequence under stirring conditions, and stir and etch for 3 hours to obtain a solid reactant III;

[0091] The power of the ultrasonic dispersion in step 4 is 180W, and the ultrasonic dispersion is performed for 90 minutes.

[0092] The concentration of the potassium permanganate solution described in step 4 is 25 mmol / L;

[0093] The mass fraction of concentrated sulfuric acid described in step 4 is 98%

[0094] 5. Wash the solid reactant III with deionized water until it is colorless and neutral, and dry it at 70° C. for 10 hours to obtain a solid reactant IV; transfer the solid reactant IV to a tube furnace, raise the temperature to 800° C. under the protection of an inert gas atmosphere, and calcine at 800° C. for 80 minutes to obtain a polypyrrole-derived carbon material;

[0095] The heating rate in step 5 is 5°C / min;

[0096] The inert gas described in step 5 is nitrogen.

[0097] Figure 5 This is a scanning electron microscope image of the polypyrrole-derived carbon material prepared in Example 3;

[0098] from Figure 5 It can be seen that when methyl orange is not used as a morphology regulator, the prepared polypyrrole-derived carbon has the morphology of nanosphere agglomerates and does not have a porous structure.

[0099] Example 4: A method for preparing a polypyrrole-derived carbon material is specifically completed by the following steps:

[0100] 1. Add methyl orange to deionized water, and then stir in a water bath at 80°C until the methyl orange is completely dissolved to obtain a methyl orange solution;

[0101] The concentration of the methyl orange solution described in step 1 is 5 mmol / L;

[0102] 2. Add 350 μL of pyrrole monomer into 100 mL of methyl orange solution, and stir the mixture for 60 min at a magnetic stirring speed of 800 r / min to obtain a mixed solution;

[0103] 3. Add ferric chloride to deionized water, and then stir the mixture under magnetic stirring at a speed of 1000 r / min for 30 min to obtain a ferric chloride solution;

[0104] The concentration of the ferric chloride solution described in step 3 is 50mmol / L;

[0105] 4. Under the condition of magnetic stirring at a speed of 800 r / min, 20 mL of ferric chloride solution was added dropwise to the mixed solution, and magnetic stirring was continued for 24 hours under the condition of magnetic stirring at a speed of 800 r / min to obtain solid reactant I; solid reactant I was washed 3 times with deionized water, and then dried at 70°C for 10 hours to obtain solid reactant II;

[0106] 5. The solid reactant II is transferred to a tube furnace, heated to 800° C. under the protection of an inert gas atmosphere, and calcined at 800° C. for 80 min to obtain a polypyrrole-derived porous carbon material;

[0107] The heating rate in step 6 is 5°C / min;

[0108] The inert gas described in step six is ​​nitrogen.

[0109] Figure 6 This is a scanning electron microscope image of the polypyrrole-derived carbon material prepared in Example 4;

[0110] from Figure 6 It can be seen that the polypyrrole-derived carbon material prepared without potassium permanganate etching is a block-like morphology without a porous structure.

[0111] Example 5: A polypyrrole-derived porous carbon material prepared in Example 1 is used to modify a zinc negative electrode, specifically by the following steps:

[0112] 1. Dispersing 90 mg of the polypyrrole-derived porous carbon material prepared in Example 1 and polyvinylidene fluoride in 100 μL of N-methylpyrrolidone to obtain a dispersion;

[0113] The mass ratio of the polypyrrole-derived porous carbon material to polyvinylidene fluoride described in step 1 is 9:1;

[0114] 2. Use sandpaper to polish the zinc negative electrode with a thickness of 100 μm to make it bright, remove the oxide layer, adjust the coating thickness of the coater to 125 μm, and then apply the dispersion to the surface of the polished zinc negative electrode, and dry it at 80°C for 12 hours to obtain a zinc negative electrode with a porous carbon coating on the surface;

[0115] In step 2, the thickness of the porous carbon coating on the surface of the zinc negative electrode is 5 μm.

[0116] The symmetrical battery assembled using the zinc negative electrode with a porous carbon coating on the surface prepared in Example 5 is specifically completed by the following steps:

[0117] ①, punching the zinc negative electrode with a porous carbon coating on the surface prepared in Example 5 into a disc with a diameter of 14 mm by a punching machine, as an electrode plate of a symmetrical battery;

[0118] ② Use a punching machine to punch the glass fiber into discs with a diameter of 16 mm as a diaphragm;

[0119] ③. The electrolyte is 2mol / L zinc sulfate electrolyte;

[0120] ④. Place the battery pole piece and diaphragm in the button battery negative electrode shell in order, add 70 microliters of electrolyte to wet the diaphragm, then add the other side electrode piece, stainless steel gasket, spring and button battery positive electrode shell, and then use a sealing machine at 50kg / cm 2 Button symmetrical battery encapsulated under pressure.

[0121] Figure 7 The symmetrical battery assembled with the zinc negative electrode having a porous carbon coating on the surface prepared in Example 5 was charged at 2 mA / cm 2 、1mAh / cm 2 Time voltage graph under test conditions;

[0122] from Figure 7 It can be seen that compared with the symmetrical battery composed of untreated pure zinc sheets, the cycle life of the symmetrical battery composed of the zinc negative electrode modified by the polypyrrole-derived porous carbon material is significantly improved, the stable cycle exceeds 900h, and the polarization voltage does not fluctuate significantly during the entire cycle, which strongly proves the cycle stability of the modified zinc negative electrode. However, compared with Example 2, the cycle life is reduced under the same discharge conditions, which is due to the reduced protective effect of the zinc negative electrode after the coating becomes thinner.

[0123] Example 6: A polypyrrole-derived porous carbon material prepared in Example 1 is used to modify a zinc negative electrode, which is specifically completed by the following steps:

[0124] 1. Dispersing 90 mg of the polypyrrole-derived porous carbon material prepared in Example 1 and polyvinylidene fluoride in 100 μL of N-methylpyrrolidone to obtain a dispersion;

[0125] The mass ratio of the polypyrrole-derived porous carbon material to polyvinylidene fluoride described in step 1 is 9:1;

[0126] 2. Use sandpaper to polish the zinc negative electrode with a thickness of 100 μm to make it bright, remove the oxide layer, adjust the coating thickness of the coater to 200 μm, and then apply the dispersion to the surface of the polished zinc negative electrode, and dry it at 80°C for 12 hours to obtain a zinc negative electrode with a porous carbon coating on the surface;

[0127] In step 2, the thickness of the porous carbon coating on the surface of the zinc negative electrode is 30 μm.

[0128] The symmetrical battery assembled using the zinc negative electrode with a porous carbon coating on the surface prepared in Example 6 is specifically completed by the following steps:

[0129] ①, punching the zinc negative electrode with a porous carbon coating on the surface prepared in Example 6 into a disc with a diameter of 14 mm by a punching machine, as an electrode sheet of a symmetrical battery;

[0130] ② Use a punching machine to punch the glass fiber into discs with a diameter of 16 mm as a diaphragm;

[0131] ③. The electrolyte is 2mol / L zinc sulfate electrolyte;

[0132] ④. Place the battery pole piece and diaphragm in the button battery negative electrode shell in order, add 70 microliters of electrolyte to wet the diaphragm, then add the other side electrode piece, stainless steel gasket, spring and button battery positive electrode shell, and then use a sealing machine at 50kg / cm 2 Button symmetrical battery encapsulated under pressure.

[0133] Figure 8 The symmetrical battery assembled with the zinc negative electrode having a porous carbon coating on the surface prepared in Example 6 was 2 、1mAh / cm 2 Time voltage graph under test conditions;

[0134] from Figure 8 It can be seen that compared with the symmetrical battery composed of untreated pure zinc sheets, the cycle life of the symmetrical battery composed of the zinc negative electrode modified by polypyrrole-derived porous carbon material is significantly improved, the stable cycle exceeds 1600h, and the polarization voltage does not fluctuate significantly during the entire cycle, which strongly proves the cycle stability of the modified zinc negative electrode. However, compared with Example 2, the cycle life is reduced under the same discharge conditions. This is because the coating is too thick, causing zinc to be mainly deposited on the electrode surface, and the coating has a limited capacity.

Claims

1. A method for preparing a polypyrrole-derived porous carbon material, characterized in that The preparation method is specifically completed in the following steps in sequence:

1. Add methyl orange to deionized water, and then stir in a water bath until the methyl orange is completely dissolved to obtain a methyl orange solution; 2. adding pyrrole monomer to methyl orange solution and stirring magnetically to obtain a mixed solution; 3. Add ferric chloride to deionized water and stir magnetically to obtain a ferric chloride solution; 4. Under magnetic stirring conditions, adding the ferric chloride solution dropwise into the mixed solution, and continuing magnetic stirring to obtain a solid reactant I; The solid reactant I is washed and dried to obtain a solid reactant II; 5. adding the solid reactant II into deionized water under ultrasonic conditions, and dispersing by ultrasonication to obtain a dispersion; Under stirring conditions, potassium permanganate solution and concentrated sulfuric acid are sequentially added to the dispersion, and stirred and etched to obtain a solid reactant III; 6. Clean and dry the solid reactant III to obtain a solid reactant IV; transfer the solid reactant IV to a tubular furnace, heat it to a calcination temperature under the protection of an inert gas atmosphere, calcine it at the calcination temperature for a period of time, grind it into particles after calcination, and obtain a polypyrrole-derived porous carbon material.

2. The method for preparing a polypyrrole-derived porous carbon material according to claim 1, characterized in that The concentration of the methyl orange solution in step 1 is 5 mmol / L to 10 mmol / L; the temperature of the water bath heating in step 1 is 60° C. to 80° C.

3. The method for preparing a polypyrrole-derived porous carbon material according to claim 1, characterized in that The volume ratio of the pyrrole monomer to the methyl orange solution in step 2 is (300 μL to 400 μL): (80 mL to 120 mL); the speed of the magnetic stirring in step 2 is 800 r / min to 1000 r / min, and the time of the magnetic stirring is 60 min to 90 min.

4. The method for preparing a polypyrrole-derived porous carbon material according to claim 1, characterized in that The concentration of the ferric chloride solution in step 3 is 40 mmol / L to 60 mmol / L; the speed of the magnetic stirring in step 3 is 500 r / min to 1000 r / min, and the time of the magnetic stirring is 10 min to 30 min.

5. The method for preparing a polypyrrole-derived porous carbon material according to claim 1, characterized in that The volume ratio of the ferric chloride solution described in step 4 to the methyl orange solution in the mixed solution is (15mL~25mL):(80mL~120mL); the speed of the continuous magnetic stirring described in step 4 is 700r / min~900r / min, and the time of continuous magnetic stirring is 24h~36h; in step 4, deionized water is used to wash the solid reactant I 3 times~5 times; the drying temperature described in step 4 is 70℃~90℃, and the drying time is 8h~10h.

6. The method for preparing a polypyrrole-derived porous carbon material according to claim 1, characterized in that The power of the ultrasonic dispersion described in step 5 is 160W~180W, and the ultrasonic dispersion time is 60min~90min; the mass ratio of the solid reactant II in the dispersion described in step 5 to the volume of deionized water is (350mg~450mg):(35mL~45mL); the concentration of the potassium permanganate solution described in step 5 is (20mmol / L~30mmol / L); the volume ratio of the potassium permanganate solution described in step 5 to the volume of the dispersion is (50mL~70mL):(30mL~50mL); the volume ratio of the concentrated sulfuric acid described in step 5 to the volume of the potassium permanganate solution is (500μL~600μL):(50mL~60mL); the mass fraction of the concentrated sulfuric acid is 90%~98%; the stirring etching time described in step 5 is 3h~6h.

7. The method for preparing a polypyrrole-derived porous carbon material according to claim 1, characterized in that In step six, the solid reactant III is washed with deionized water until it is colorless and neutral; the drying temperature in step six is ​​60°C to 80°C, and the drying time is 10h to 16h; the heating rate in step six is ​​2°C / min to 10°C / min; the calcination temperature in step six is ​​700°C to 900°C, and the calcination time is 60min to 100min; the inert gas in step six is ​​nitrogen, argon or helium.

8. Use of a polypyrrole-derived porous carbon material prepared by the preparation method according to claim 1, characterized in that A polypyrrole-derived porous carbon material is used to modify zinc anode.

9. Use of a polypyrrole-derived porous carbon material prepared by the preparation method according to claim 8, characterized in that A polypyrrole-derived porous carbon material is used to modify a zinc negative electrode, which is specifically completed by the following steps:

1. dispersing a polypyrrole-derived porous carbon material and a binder in a solvent to obtain a dispersion; The solvent in step 1 is one or a mixture of several of N-methylpyrrolidone, dimethyl sulfoxide, acetonitrile, dichloromethane and ethanol; The binder in step 1 is one or a mixture of polyvinylidene fluoride, polyacrylic acid and polyurethane; The mass ratio of the polypyrrole-derived porous carbon material to the binder in step 1 is (8-9):(1-2); Step 1: The mass fraction of the polypyrrole-derived porous carbon material in the dispersion is 60% to 70%; 2. coating the dispersion onto the surface of the zinc negative electrode and drying it to obtain a zinc negative electrode having a porous carbon coating on the surface; The drying temperature in step 2 is 60°C to 80°C; In step 2, the thickness of the porous carbon coating on the surface of the zinc negative electrode is 5 μm to 30 μm.

10. Use of a polypyrrole-derived porous carbon material prepared by the preparation method according to claim 8, characterized in that The zinc negative electrode with a porous carbon coating on its surface is used as the negative electrode of an aqueous zinc ion battery.

Citation Information

Patent Citations

  • Method for manufacturing amorphous carbon and multi-walled carbon nano-tube composite electrode materials on basis of polypyrrole carbonization

    CN105118997A

  • Metal zinc negative electrode having functional interface modification layer and preparation method and application thereof

    CN109713213A

  • Preparation method of nitrogen-doped porous carbon material, prepared porous carbon material and application thereof

    CN112573503A

  • Carbon-based electrode material with ultrahigh specific capacitance and preparation method thereof

    CN115240989A

  • Preparation method of carbon cloth electrodeposition polypyrrole supercapacitor negative electrode material

    CN115295320A